2021
DOI: 10.1155/2021/6630938
|View full text |Cite
|
Sign up to set email alerts
|

An Inventory Model for Perishable Items with Price-, Stock-, and Time-Dependent Demand Rate considering Shelf-Life and Nonlinear Holding Costs

Abstract: Nowadays, consumers are more health conscious than before, and their demand of fresh items has intensely increased. In this context, an effective and efficient inventory management of the perishable items is needed in order to avoid the relevant losses due to their deterioration. Furthermore, the demand of products is influenced by several factors such as price, stock, and freshness state, among others. Hence, this research work develops an inventory model for perishable items, constrained by both physical and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Agrawal and Yadav [ 56 ] studied SCs that considered price-dependent demands to simultaneously define the production, inventory, and pricing decisions. Macias-Lopez et al [ 57 ] developed an inventory model where both the physical and freshness depreciations were constrained. The demand for perishable products is a multivariate function of freshness, current inventory level, and price.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Agrawal and Yadav [ 56 ] studied SCs that considered price-dependent demands to simultaneously define the production, inventory, and pricing decisions. Macias-Lopez et al [ 57 ] developed an inventory model where both the physical and freshness depreciations were constrained. The demand for perishable products is a multivariate function of freshness, current inventory level, and price.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This reason lead to lots of research in developing efficient models for profit maximization. In the quest to provide retailers with efficient decision making mechanism, [6] developed an inventory model for perishable items with price and stock-level dependent demand rate,taking into consideration the shelflife and a non-linear holding cost. Six different price dependent function where 45 tested on the model and showed that the profit function of the retailer business is concave meaning there is a unique Nathaniel Kayode Oladejo 1 , IJMCR Volume 11 Issue 01 January 2023…”
Section: Literature Reviewmentioning
confidence: 99%
“…It capitalizes later by inventory researchers employing some realistic assumptions, for example, stock of products, discount policy, effects of time, and many other widely used attributes in the field of supply chain management. Sometimes a large inventory of products in any store can entice customers and produce higher demand than usual (Macías-López et al 2021;Chang et al 2010). In this direction, (Gupta and Vrat 1986) was the pioneer to explore the first inventory model with a stock-dependent demand rate.…”
Section: Influence Of Stock Dependent Demand On Traditional Inventory Modelmentioning
confidence: 99%
“…As consumers are now more health-conscious than ever before, the demand for fresh items has increased sharply. Based on this concept, (Macías-López et al 2021) developed a model for perishable items that emphasizes customer demand with product quality over time. The demand here is considered with selling price and available stock dependent.…”
Section: Influence Of Sensitiveness Of Time On Traditional Inventory Modementioning
confidence: 99%